Efektivitas Program Pengadaan Laptop Untuk Siswa Sekolah Dasar Dalam Peningkatan Kualitas Pendidikan di Kabupaten Badung (Studi Pada SD No. 1 Tuban) - Budianti, Ni Putu Rika; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2020)
ABSTRACT Notebook procurement programs for basic school students is one of the top programooftthe governmentoofBBadungRRegency with a mission to improve education. This research uses descriptive qualitative methods through interviews, observations and documentation asttheemainddata management techniques.sTherresults oftthissstudysshowtthat there are still a few things that the Education, Youth and Sport Goverment Agency of Badung Regency should take into account, among the problem of achieving program’s goal. Supporting factors such as computer teacher and wi-fi support facilities must still be improved inoorderrtommaketthe goal ofythe program. Theeobstacles that stand at SD No.1 Tuban, there are no teachers of computer subjects particularly at SD No.1 Tuban, the ability of a homeroom teacher to operate the notebook is still weak and there is no timeline learning. Keywords: Effectiveness, Program, Notebook Procurement